Translating Research into Clinical Scale Manufacturing of Mesenchymal Stromal Cells - Karen Bieback; Sven Kinzebach; Marianna Karagianni (Stem Cells International)
It sounds simple to obtain sufficient numbers of cells derived from fetal or adult human tissues, isolate and/or expand the stem cells, and then transplant an appropriate number of these cells into the patient at the correct location. However, translating basic research into routine therapies is a complex multistep process which necessitates product regulation. The challenge relates to managing the expected therapeutic benefits with the potential risks and to balance the fast move to clinical trials with time-consuming cautious risk assessment. This paper will focus on the definition of mesenchymal stromal cells (MSCs), and challenges and achievements in the manufacturing process enabling their use in clinical studies. It will allude to different cellular sources, special capacities of MSCs, but also to current regulations, with a special focus on accessory material of human or animal origin, like media supplements. As cellular integrity and purity, formulation and lot release testing of the final product, validation of all procedures, and quality assurance are of utmost necessity, these topics will be addressed.